PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA MIND MAPPING TERHADAP HASIL BELAJAR SUBTEMA KEBERAGAMAN BUDAYA BANGSAKU - Rachmafadia Azzahra; Yuyun Elizabeth Patras; Nur Hikmah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research is a quasi-experimental research. This study aims to find out the differences and advantages of learning outcomes in the sub-theme of cultural diversity of my nation. The calculation of the N-Gain model of Problem Based Learning is 60 with medium criteria, the N-Gain value of the conventional model is 59 with medium criteria. So that the N-Gain in the experimental class with the Problem Based Learning model is greater than the control class with the conventional model. In the hypothesis test, the calculation results were obtained of 1,998 and ttabel of 4,541, which means that the count is not located between -1,998 < the calculation < ttabel, it shows that H0 is rejected, and Ha is accepted. Based on the results of the research above, it can be stated that Problem Based Learning has differences in the learning outcomes of the sub-theme of cultural diversity of my nation.